Methodological and project process for product design in SAVELIGHT project - Quintero Diaztagle, Carlos Andrés; Universidad Católica de Pereira (Universidad Católica de Pereira, 2016)
This article is part of the research project "SAVE LIGHT" Design and development of new product related to green energy and energy saving products. The project is carried out within the Young Researches and innovators program  at COLCIENCIAS 566 in 2012. In conjunction with the company Greenlogy, in order to develop a product that extends the user interaction with automation lighting systems that can be marketed whitin the product portfolio of the company. It arises under the exploratory methodology throught the design, with an applied qualitative and project type, defining different characteristics (aesthetic, production usability, etc.) with the aim of developing indoor lighting products whitin a multidisciplinary project approach.